Protein S100 sebagai Petanda Kerusakan Otak pada Cedera Otak Ringan dan Sedang - Aditarahma Imaningdyah; Marzuki Suryaatmadja; Lyna Soertidewi Kiemas (Majalah Sainstekes, 2017)
Brain injury becomes worldwide public health issue since it may cause disability and mortality. The diagnosis of brain injury is made based on clinical neurology examination, and CT scan or MRI. Serum S100 protein examination in mild and moderate brain injury patients is needed to detect and evaluate the presence of post traumatic brain injury. This research subject is healthy people and patients with mild and moderate brain injury, based on their GCS grade, clinical neurologic examination, and CT scan. On these patients, the blood for S100 protein examination is taken at admission, 6 and 24 hours post trauma, and last day of hospitalization. Examination of a serum S100 protein is conducted using ECLIA method. There is significant difference (p value 0,001) in mild or moderate brain injury patients in all serum S100 protein. The peak level of serum S100 protein reached at 6 hours post trauma. Serum S100 protein in moderate brain injury patients at admission is significantly higher than the mild ones, and serum S100 protein in mild brain injury patients is also significantly higher than healthy people. Serum S100 protein can be used as brain injury biomarker  to  detect  and  evaluate  the  presence  of  post  traumatic  brain injury.